Firearm screening and secure storage counseling among home visiting providers: a cross-sectional study of SafeCare® providers in the U.S. - Melissa C. Osborne; Kate Guastaferro; Shelden Banks; Hari Vedantam; Shannon Self-Brown; Shannon Self-Brown (Frontiers in Public Health, 2024)
BackgroundFirearms used in pediatric firearm deaths are most often obtained from the child’s home, making secure firearm storage initiatives imperative in prevention efforts. Evidence-based home visiting (EBHV) programs are implemented with over 277,000 families annually, providing an opportunity for secure firearm storage counseling. The purpose of this study was to assess EBHV providers’ experiences with firearm screening (“assessment”), secure storage counseling, and their perceptions for related training needs.MethodsProviders in the U.S. from SafeCare®, an EBHV program often implemented with families experiencing increased risk of child neglect and physical or emotional abuse, were invited to participate in a survey to examine firearm assessment and attitudes toward and experiences with firearm safety counseling. Survey items were primarily Likert scale ratings to indicate level of agreement, with some open-ended follow-up questions. Descriptive statistics (i.e., frequencies and percentages) were used to report item-level agreement. A post hoc analysis was conducted using Spearman correlation to examine the association between assessment and counseling and provider-level factors.ResultsSixty-three SafeCare providers consented to and completed the survey items. Almost three-quarters (74.6%) agreed/strongly agreed that they assess in-home firearm availability. However, 66.7% agreed/strongly agreed that they have not been adequately trained to discuss firearm safety topics. A substantial proportion (80.6%) indicated they would counsel more if materials and training on this topic were available. Response variability emerged by level of urbanicity. A post hoc analysis found that providers’ self-reported frequency of assessment and counseling were associated with their comfort level discussing firearm safety and whether or not they had worked with families impacted by firearm injury.ConclusionSafeCare providers report a need for materials and training on secure firearm storage, and a willingness to provide more counseling with proper training to the families they serve. Findings illuminate the need for secure storage initiatives for EBHV programs, which have broad service reach to a substantial number of at-risk U.S. families annually.